PERENCANAAN DELIBERATIF DALAM PEMBUATAN KEBIJAKAN DESA - Rahmat Rafinzar; Khairunnas Khairunnas (Prodi Ilmu Pemerintahan FISIP Universitas Komputer Indonesia, 2023)
This study aims to see the implementation of village development planning with the principles of deliberative democracy and assess the implementation of sub-district village development planning in Pulau Rimau District, Banyuasin Regency, South Sumatra. This study uses a descriptive research method with a qualitative approach. The data analysis techniques used by the researchers are interactive models from Miles and Huberman. This study indicates that the implementation of the principles of deliberative democracy in village development planning is weak because it still has problems in reporting and realizing the proposed results of village development planning. As well as community involvement that is not comprehensive in the process of implementing village development planning, this is contrary to the principles of deliberative democracy which prioritize optimizing the role of the community in the process. However, the notion of deliberation may be applied in representative democracy at the level, in other words, the process of forming or making policies by representatives of village communities is colored by the involvement of the people/constituents through a deliberative process. For this reason, special assistance from the government is needed to form competent village community representatives in the village development planning deliberation. Keywords: Deliberative, Village Development Planning, Public Participation.